No time for Hallie - Hapka, Catherine; Regan, Dana (White Plains, New York : Studio Fun, 2015)
"Zach's neighbors just had a new baby--and now they're threatening to take their cat, Hallie, to the animal shelter. The kids have been volunteering there since starting the Pet Rescue Club, and they know an older cat might have trouble getting adopted. Can they convince the family to give their kitty another chance--or maybe find someone who truly appreciates all that an older kitty has to offer?"--
At head of title: ASPCA kids.
Based on a real-life cat named Hallie.
"Based on a true story"--Cover.
Keywords: Cats -- Fiction; Pets -- Fiction; Pet adoption -- Fiction; Animal shelters -- Fiction; Clubs -- Fiction